2020
DOI: 10.1111/acer.14418
|View full text |Cite
|
Sign up to set email alerts
|

Selective Deficits in Contingency‐Driven Ethanol Seeking Following Chronic Ethanol Exposure in Male Mice

Abstract: Background People with alcohol use disorders exhibit an overreliance on habitual response strategies which may result from a history of chronic alcohol exposure. Although habits are defined by behavior that persists despite changes in outcome value and in action–outcome relationships, most research investigating the effects of ethanol exposure on habits has focused only on outcome devaluation. A clear understanding of the effects of chronic alcohol exposure on the ability to flexibly update behavior may provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 36 publications
1
20
1
Order By: Relevance
“…Thus, CIE mice were able to acquire lever pressing for food relying on neural mechanisms supporting habit learning. Recent findings corroborate the observed lack of goal-directed control in CIE mice (M. F. Lopez et al, 2014;Renteria et al, 2018Renteria et al, , 2020Barker et al, 2020) and with the disruption to decision-making control observed under different instrumental tasks and varied tests of goal-directed control. Our work adds to an ever-growing body of research on such decisionmaking deficits and highlights the importance of examining alcohol-induced alterations to neural circuits and mechanisms controlling goal-directed processes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, CIE mice were able to acquire lever pressing for food relying on neural mechanisms supporting habit learning. Recent findings corroborate the observed lack of goal-directed control in CIE mice (M. F. Lopez et al, 2014;Renteria et al, 2018Renteria et al, , 2020Barker et al, 2020) and with the disruption to decision-making control observed under different instrumental tasks and varied tests of goal-directed control. Our work adds to an ever-growing body of research on such decisionmaking deficits and highlights the importance of examining alcohol-induced alterations to neural circuits and mechanisms controlling goal-directed processes.…”
Section: Discussionsupporting
confidence: 81%
“…The structure of the task allows us to look at OFC activity at the onset, during, and offset of lever presses, as well as during outcome-related epochs. Prior works have found that alcohol-exposed rats and mice show similar acquisition of lever-press performance compared with naive controls, but outcome devaluation and contingency degradation procedures ( Corbit et al, 2012 ; Lopez et al, 2014 ; Morisot et al, 2019 ; Renteria et al, 2018 ; Barker et al, 2020 ) have shown that such lever pressing is controlled by habitual, instead of goal-directed, processes. Thus, in a subset of mice, we performed outcome devaluation testing procedures after acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Hence our action differentiation task was shown to effectively isolate instrumental learning contingency processes from those crucial for updating and inferring value representations, with the unique feature of doing so in a completely self-paced manner that requires an animal to continuously infer contingency durations to guide their behavior. In contrast to recent findings (Barker et al, 2020), the comparable levels of performance in our task, and the differences observed following outcome devaluation, suggests that the effects of alcohol dependence on behavioral control might be somewhat limited to those requiring outcome evaluation processes. However, Barker et al examined degradation of the contingency in contrast to acquisition and performance effects examined here.…”
Section: Discussioncontrasting
confidence: 99%
“…Prior works have suggested that alcohol dependent rats and mice show largely similar acquisition of lever-press performance compared to naïve controls, but outcome devaluation procedures (Corbit et al, 2012; M. F. Lopez et al, 2014; Morisot et al, 2019; Renteria et al, 2018, 2020), and more recently, contingency degradation procedures (Barker et al, 2020), have shown lever pressing is under habitual control. We found that daily performance in our contingency task was largely intact in alcohol dependent mice; however, subsequent devaluation testing recapitulated the dependence-induced reduced sensitivity to outcome devaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, after an extended period of self-administration, alcohol consumption will continue even if mixed with aversive quinine concentrations [61,62]. Subsequent studies have shown that chronic intermittent ethanol exposure results in habitual alcohol seeking in rodents, as assessed with both outcome devaluation [63,64] and contingency degradation [65] procedures. Yet, alcohol further affects rodent goal-directed behavior, with acute intoxication [66], chronic ethanol exposure [67] as well as contextual conditioning to alcohol [68] decreasing sensitivity to devaluation of non-alcoholic outcomes.…”
Section: Findings In Alcohol Use Disorder and At-risk Populationsmentioning
confidence: 99%